Who Am I? Identity as a Task in Times of Rapid Social Change - Mirosław Józef Szymański (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The question: who am I? - is one of the most frequently formulated questions of an existential nature. In the period of rapid social change it becomes more and more insistent. In recent decades, changes occurring in various areas of life have assumed a truly revolutionary character. A change that seems particularly prominent is globalisation. Rapid social changes force one to form the individual self. This is not an easy task, therefore many people experience identity dilemmas. These are deepened by diverse, often inconsistent or even contradictory, standards and expectations of institutions and social groups in the functioning of which they participate. The liberation of individualism characterising modern and post-modern times increases a sense of subjectivity of individuals, yet at the same time it subjects them to states of uncertainty and crisis. Anthony Giddens claims that they are expressed by the opposing dimensions of contemporary reality such as: unification vs. fragmentation, powerlessness vs. appropriation, authority vs. uncertainty, personalised vs. commodified experience. Therefore, the construction of identity becomes an important task to be undertaken by an individual and one that requires pedagogical support.